Supported nano-sized gold catalysts for selective reduction of 4,4'-dinitrostilbene-2,2'-disulfonic acid using different reductants - Chen, Y.; Peng, Wenchao.; Wang, Shaobin; Zhang, F.; Zhang, G.; Fan, X. (Elsevier, 2012)
Gold nanoparticles supported on three metal oxides, TiO2, Al2O3 and Fe2O3, were prepared by a modified precipitation-deposition method using urea as an additive. These catalysts were tested in chemoselective reduction of 4,4’-dinitrostilbene-2,2’-disulfonic acid to 4,4’-diaminostilbene-2,2’-disulfonic acid. Three reagents, hydrogen, carbon monoxide, and sodium formate, were employed as reductants. It was found that >94% of the nitrostilbene was transformed into the aminostilbene without the reduction of olefinic group. In addition, these catalysts exhibited stable performance after regeneration by calcination at 400 °C for 5 h. This clean approach provides a promising application for synthesis of amino substituted stilbene sulfonic acid on an industrial scale.